Ang sabi ni nanay, and sabi ni tatay - Calagopi, Sacha (UNICEF, 2015)
"Mother teaches Rosalie to clean, go to amrket, and to laundry. Meanwhile, father trains Francis to do minor repairs and wash the car."--Page 4 of cover.